Wretched of the earth - Fanon, Frantz (Middlesex, 1958)
speaker includes himself with his fellow-countrymen. And then, usually, he adds Unless ... His meaning is clear; no more mistakes must be made; if his instructions are not carried out to the letter, then and only then will the country go to pieces. In short, it is a threat followed by a piece of advice and these remarks are so much the less shocking in that they spring from a national intersubjectivity. But on the contrary when Fanon says of Europe that she is rushing to her doom, far from sounding the alarm he is merely setting out a diagnosis. This doctor neither claims that she is a hopeless case - miracles have been known to exist-nor does he give her the means to cure herself. He certifies that she is dying, on external evidence, founded on symptoms that he can observe. As to curing her, no; he has other things to think about; he does not give a damn whether she lives or dies. Because of this, his book is scandalous. And if you murmur, jokingly embarrassed, 'He has it in for us!' the true nature of the scandal escapes you; for Fanon has nothing in for you at all; his work-red-hot for some - in what concerns you is as cold as ice; he speaks of you often, never to you. The black Goncourts and the yellow Nobels are finished; the days of colonized laureats are over. An ex-native, French-speaking, bends that language to new requirements, makes use of it, and speaks to the colonized only: "Natives of all under-developed countries, unite!' What a downfall! For the fathers, we alone were the speakers; the sons no longer even consider us as valid intermediaries: we are the objects of their speeches. Of course, Fanon mentions in passing our well-known crimes: Sétif, Hanoi, Madagascar: but he does not waste his time in condemning them; he uses them. If he demonstrates the tactics of colonialism, the complex play of relations which unite and oppose the colonists to the people of the mother country, it is for his brothers; his aim is to teach them to beat us at our own game.
Keywords: Political Science